ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИДА ПЕДАГОГИК ЖАРАЁНЛАРНИ БОШҚАРИШ ТАМОЙИЛЛАРИ ВА КОНЦЕПТУАЛ АСОСЛАРИ - Норова, К.Ю. (SCIENCE and SOCIETY, 2020)
In the management of pedagogical processes in higher education institutions, it is important to train future professionals with high potential who can compete and meet world standards. Therefore, the management and organization in pedagogical processes in terms of teaching the course "Education Management" in higher education institutions is important.
Keywords: principle; conceptual framework; education management; cooperation; management; innovation; pedagogical process; subject; system